Brand-Based Innovation: Relational Perspectives on Brand Logics and Design Innovation Strategies and Implementation - Nicky Nedergaard (Copenhagen Business School (CBS), 2014)
With the primary ambition to contribute to the brand orientation literature this thesis explores relationships between corporate brand identities and the management of design innovation. The thesis is based partly on a prolonged empirical case study of Bang & Olufsen and partly on a multiple case study of small and medium sized design-oriented firms – all characterised by a strategic focus on managing market-driving innovation. Grounded in an interpretive analytical approach the thesis examines how corporate brand identity as a strategic logic of the firm affects flows of management decisions and the structuring of design innovation strategies and implementation hereof. The thesis' theoretical foundation is anchored in the competence-based view on firm competitiveness. This foundation is complemented by institutional and organisational culture theories to the purpose of uncovering how organisational decision-makers are affected by corporate brand logics in relation to the management of design innovation processes and capabilities. The thesis presents four papers, which contribute conceptually and empirically to advance the brand orientation literature from a competence-based perspective focused on design and innovation management. Overall, findings suggest that corporate brand identity as a competitive logic in brand- and design-oriented firms can guide innovation strategy and decisions for coordinating management processes and the use of resources to develop brandsupportive innovation capabilities. However, it is also suggested that such brand logics should be complemented by market logics in a dynamic interplay. In this way a more pragmatic approach is achieved to the sustainment of innovation capabilities, which in an integrative manner support firm corporate brand identity and market adaptability as complementary management foci for customer value creation and sustained competitive advantages.
hdl:10398/9036
Keywords: 650